Beyond the jump scare: Sacred pedagogy, moral negotiation, and postmodern audience agency in Indonesian horror trailer discourse - Nainggolan, Paulina; Rahyadi, Irmawan (Universitas Bunda Mulia, 2026)
Indonesian horror cinema is increasingly embedded in religious discourse, yet scholarly attention has focused predominantly on film texts rather than audience-generated meaning-making. This study investigates how Indonesian viewers engage with religious horror on YouTube, specifically how they construct moral and theological meanings through trailer comment sections. Drawing on an empirical dataset of 600 systematically sampled YouTube comments from the official trailers of Siksa Kubur (2024), Kuasa Gelap (2024), and Qodrat 2 (2025), collected on 25 June 2025, the study employs inductive thematic analysis informed by audience reception theory, digital religion studies, and narrative persuasion theory. Five key themes emerged: (1) sacred pedagogy, in which audiences treat horror as a medium of moral and religious instruction; (2) digital access rituals, revealing tensions between content accessibility and authentic viewing; (3) emotional alchemy, whereby fear is reinterpreted as a catalyst for spiritual reflection; (4) critical audience posture, with viewers actively evaluating theological accuracy and cultural authenticity; and (5) the formation of